População e governo: vulnerabilidade à COVID-19 e intervenções públicas no enfrentamento da doença no Ceará - Brito, Ana Vládia da Costa (2022)
The general objective of this thesis was to analyze the behavior of the population and the government in the face of COVID-19, using the State of Ceará as a cutout. From the population’s perspective, we sought to identify the factors that make people more or less vulnerable to the disease. From the government's perspective, the focus was on analyzing the measures implemented by the municipal authorities and their effectiveness in controlling epidemiological indicators. The presentation of the analyses is structured in three chapters. The first of them identified the main vulnerability factors and the most vulnerable groups to COVID19 in the Metropolitan Region of Fortaleza (RMF), based on an online survey with 437 residents. As methods of data analysis, descriptive and inferential statistical techniques were used. The concept of vulnerability was operationalized through the construction of the COVID19 Vulnerability Index (IVC-19). In the second article, the objective was to analyze the importance of the measures implemented by the municipal government in the face of COVID19 in Ceará. For that, three groups of information were used. The first refers to the indicators number of confirmed cases of COVID-19, number of deaths and lethality in each municipality. The second refers to measures to combat COVID-19: containment measures (8 measures), social protection measures (9 measures) and measures to support health services (8 measures) totaling 25 measures, and the third, with the objective of to incorporate socioeconomic characteristics into the study: GDP “per capita”, population density and HDI. The degree of implementation of measures to combat COVID-19 was measured by aggregating the 25 measures into an index. The impact of the measures on the epidemiological indicators was estimated by regression models in a short and medium term perspective. The objective of the third article was to analyze the trend of sustainable development indicators in the municipalities of Ceará from 2017 to 2021. For that, an analysis of the growth rates of a set of thirty indicators was carried out and a measure of development setback was estimated. relative to the prepandemic and pandemic periods. The results showed that the pandemic, despite its implications for the health of the population, cannot be separated from socioeconomic aspects. It was observed that vulnerability to COVID-19 is manifested differently between groups of society, with young people up to 30 years old, those with lower income and education levels, brown, black, Asian, and indigenous communities, and the unmarried more vulnerable. In this sense, measures to deal with COVID-19 must especially contemplate this portion of individuals. The results of the second article drew attention to the fact that the measures to combat the disease were mainly aimed at containing it, while the social protection measures, which could mitigate and make the aforementioned groups less vulnerable, had a low level of implementation by municipal managers. In addition, it was possible to observe that the socioeconomic characteristics of the municipalities proved to be more determinant to influence the behavior of epidemiological indicators than the coping measures as a whole. Thus, it was noticed that the action of local governments should be directed towards disease prevention strategies and encouraging the development indicators of the municipality. Local socio-economic conditions must be improved to prevent a repetition of the drama experienced with COVID-19. This task for managers will be arduous in the post-COVID-19 period, since, as observed in the results of the third article, municipalities in Ceará, with different magnitudes, showed setback in different dimensions.